(m-4)(3m-10)=3(m-2)+18

Simple and best practice solution for (m-4)(3m-10)=3(m-2)+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (m-4)(3m-10)=3(m-2)+18 equation:


Simplifying
(m + -4)(3m + -10) = 3(m + -2) + 18

Reorder the terms:
(-4 + m)(3m + -10) = 3(m + -2) + 18

Reorder the terms:
(-4 + m)(-10 + 3m) = 3(m + -2) + 18

Multiply (-4 + m) * (-10 + 3m)
(-4(-10 + 3m) + m(-10 + 3m)) = 3(m + -2) + 18
((-10 * -4 + 3m * -4) + m(-10 + 3m)) = 3(m + -2) + 18
((40 + -12m) + m(-10 + 3m)) = 3(m + -2) + 18
(40 + -12m + (-10 * m + 3m * m)) = 3(m + -2) + 18
(40 + -12m + (-10m + 3m2)) = 3(m + -2) + 18

Combine like terms: -12m + -10m = -22m
(40 + -22m + 3m2) = 3(m + -2) + 18

Reorder the terms:
40 + -22m + 3m2 = 3(-2 + m) + 18
40 + -22m + 3m2 = (-2 * 3 + m * 3) + 18
40 + -22m + 3m2 = (-6 + 3m) + 18

Reorder the terms:
40 + -22m + 3m2 = -6 + 18 + 3m

Combine like terms: -6 + 18 = 12
40 + -22m + 3m2 = 12 + 3m

Solving
40 + -22m + 3m2 = 12 + 3m

Solving for variable 'm'.

Reorder the terms:
40 + -12 + -22m + -3m + 3m2 = 12 + 3m + -12 + -3m

Combine like terms: 40 + -12 = 28
28 + -22m + -3m + 3m2 = 12 + 3m + -12 + -3m

Combine like terms: -22m + -3m = -25m
28 + -25m + 3m2 = 12 + 3m + -12 + -3m

Reorder the terms:
28 + -25m + 3m2 = 12 + -12 + 3m + -3m

Combine like terms: 12 + -12 = 0
28 + -25m + 3m2 = 0 + 3m + -3m
28 + -25m + 3m2 = 3m + -3m

Combine like terms: 3m + -3m = 0
28 + -25m + 3m2 = 0

Factor a trinomial.
(4 + -3m)(7 + -1m) = 0

Subproblem 1

Set the factor '(4 + -3m)' equal to zero and attempt to solve: Simplifying 4 + -3m = 0 Solving 4 + -3m = 0 Move all terms containing m to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3m = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3m = 0 + -4 -3m = 0 + -4 Combine like terms: 0 + -4 = -4 -3m = -4 Divide each side by '-3'. m = 1.333333333 Simplifying m = 1.333333333

Subproblem 2

Set the factor '(7 + -1m)' equal to zero and attempt to solve: Simplifying 7 + -1m = 0 Solving 7 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1m = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1m = 0 + -7 -1m = 0 + -7 Combine like terms: 0 + -7 = -7 -1m = -7 Divide each side by '-1'. m = 7 Simplifying m = 7

Solution

m = {1.333333333, 7}

See similar equations:

| 4x^2-36x-5=0 | | -14=4y+3y | | x+5=x-9 | | 2x+3=2x-9 | | 1x+6y=10 | | (2x^2+9x-1)+(3x^2+6x+18)-(5x^2-12)= | | x*x=8 | | 2069321459+2069321459= | | 1x-6y=10 | | x*x*x=8 | | -1+14x=13x+17 | | Ax-Gy=L | | Y^2-6V+9=0 | | x*x-2=142 | | 8000+10000+9000= | | x*x-2=2 | | 2(4+3)=x | | 7323+11390+8929= | | 6x=25y+11 | | 0.375-0.5t=0.1875 | | 134+29= | | 2.6666666667c+0.333333333=0.8333333333 | | -6u=-10 | | 25+24+x= | | 3y=20 | | v^2+2v-4=0 | | v^2+2-4=0 | | 0.15*x+x=76759.3 | | 4(4x+2)-8(x-2)=3(2x+1)-2 | | 15d+15=57 | | 4(4x+2)-8(k-2)=3(2x+1)-2 | | 0.15Xm+m=76759.3 |

Equations solver categories